GREEN SYNTHESIS AND CHARACTERIZATION OF MARINE YEAST-MEDIATED SILVER AND ZINC OXIDE NANOPARTICLES AND ASSESSMENT OF THEIR ANTIOXIDANT ACTIVITY - R, Aswathy; B, Gabylis; S, Anwesha; Kv, Bhaskara Rao (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The present study focuses on the synthesis of silver and zinc oxide (ZnO) nanoparticles from marine yeasts, isolated from the sediments of the Bay of Bengal, Bakkhali coast, West Bengal, and India. Methods: The marine sediment samples were diluted through serial diution and cultured onto yeast malt agar medium by the spread plate method. The selected yeast isolates were screened for the biosynthesis of silver and ZnO nanoparticles. Characterization of both the nanoparticles was done by applying ultraviolet (UV)-visible spectroscopy, atomic force microscopy, scanning electron microscopy, and Fourier transform infrared spectroscopy. Results: A total of five marine yeasts isolates were able to synthesize silver and ZnO nanoparticles as evidence of the color change. Optical density was measured in UV-spectrometer at different time interval for the conformation of production of nanoparticles. The size of silver nanoparticle was 31.78 nm and ZnO nanoparticle was 86.27 nm. The synthesized nanoparticles are then used for antioxidant assays. Conclusions: We are concluding that marine yeast isolates SAG1 and SAG2 both are potential marine yeast isolates which can synthesize both the silver and ZnO nanoparticles. They also showed good antioxidant activity.